Anhydride-cured epoxy resin reinforcing with citric acid-modified cellulose. (August 2020) - Hsu, Yu-I; Huang, Lulu; Asoh, Taka-Aki; Uyama, Hiroshi
Abstract: Herein, improvement of the mechanical properties of epoxy resin by compositing with citric acid modified cellulose (CAC) was reported. CAC were prepared from carboxyl functionalization with citric acid to increase the adhesion between cellulose and epoxy resin. The epoxy resin composites were prepared using 2, 2-bis (4-glycidyloxyphenyl) propane (BADGE) as component, 4-methylcyclohexane-1, 2-dicarboxylic anhydride (MHHPA) as curing agent, and cellulose or CAC as filler. The tensile strength of cellulose/epoxy resin composites were decreased with the content of cellulose increased. On the other hand, the tensile strength of CAC/epoxy resin composites were effectively increased with the content of CAC increased. Moreover, compared with pure epoxy resins and cellulose/epoxy resin composites, the Young's modulus and the toughness of CAC/epoxy resin composites significantly increased with the presence of 10 wt% CAC. SEM images showed that cellulose agglomerated in epoxy resins, in contrast, CAC dispersed uniformly in epoxy resins, determined that the adhesion between CAC and epoxy resins were improved after introduced carboxyl groups to cellulose lead to the mechanical properties improved. CAC was also used to partly replace MHHPA to decrease the usage of toxic curing agent, and the mechanical properties of CAC/epoxy resin composites increased with lower MHHPA content. These results indicated that CAC can partially take place of the conventional curing agent in composite preparation, which may further decrease the production cost and improve the mechanical properties of product. Highlights: CAC was prepared by carboxyl functionalization of cellulose with citric acid. Adhesion between CAC and epoxy resin increased because of carboxyl groups. Mechanical properties of epoxy resin were augmented by compositing CAC. CAC can partially replace the conventional curing agent in composite preparation.